Implementation of online single submission risk based approach (OSS-RBA) policy in business licensing - Damayanti, Maya; Jeddawi, Murtir; Arsyad, Romly; Sahyana, Yana (International Journal Labs, 2023)
The aim of this research is to analyze the implementation of the OSS-RBA policy in risk-based business licensing in Cirebon City, West Java Province and to formulate the relationship between central, provincial, district/city government authority in implementing the OSS-RBA policy in risk-based business licensing in Cirebon City, Java Province. West. This research uses the policy implementation theory developed by Grindle which consists of policy content and policy context. The research approach used in this research is a qualitative approach with a descriptive type of research. The data analysis technique used is by data reduction and conclusion withdrawal. The research results show that the implementation of the OSS-RBA policy in risk-based business licensing in Cirebon City is not optimal. The OSS-RBA service in risk-based business licensing in Cirebon City has not been communicated well to employees and the public so that there are still many process obstacles faced, from the aspect of policy content there are also too many derivative technical policies that regulate it, resulting in the OSS-RBA policy being ineffective. The OSS-RBA policy model in risk-based business licensing in Cirebon City, the key implication of Grindle's theory of policy implementation, is that there is an additional dimension of action. The implication of the theory developed by researchers is based on research results that to achieve service goals, the dimensions of Coordination, Communication and Commitment need to be added.